Parmenides: Sounds, Images, Experience. A Suggestion of a New Reading - Fratticci, Walter (Peitho. Examina Antiqua, 2015)
This essay aims to analyse the Parmenides’ interpretation that Laura Gemelli Marciano offered in the Eleatica lectures. The scholar represents the Parmenidean Poem as a mystical experience where sounds, words and images communicate and produce a real approach to the divine reality at the same time. This intriguing reading, which closely follows that offered by Kingsley, understimates the problems and cognitive structures of rational thought in the poem. Thus Parmenides appears to be a shaman rather a philosopher.